2018
DOI: 10.1039/c8an00231b
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandex vivomeasurement of the biophysical properties of blood using microfluidic platforms and animal models

Abstract: Haemorheologically impaired microcirculation, such as blood clotting or abnormal blood flow, causes interrupted blood flows in vascular networks. The biophysical properties of blood, including blood viscosity, blood viscoelasticity, haematocrit, red blood bell (RBC) aggregation, erythrocyte sedimentation rate and RBC deformability, have been used to monitor haematological diseases. In this review, we summarise several techniques for measuring haemorheological properties, such as blood viscosity, RBC deformabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 135 publications
1
33
0
Order By: Relevance
“…The previous study has reported that biophysical properties of blood samples (hematocrit (Hct), viscosity, and erythrocyte sedimentation rate (ESR)) are strongly correlated with coronary heart diseases [3]. Thereafter, the biophysical properties of the blood sample have been studied extensively for the effective monitoring of circulatory disorders [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The previous study has reported that biophysical properties of blood samples (hematocrit (Hct), viscosity, and erythrocyte sedimentation rate (ESR)) are strongly correlated with coronary heart diseases [3]. Thereafter, the biophysical properties of the blood sample have been studied extensively for the effective monitoring of circulatory disorders [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microfluidic devices that mimic vessel branching, shortening, and compression coupled with a simple image analysis algorithm address this issue and provide a simple solution to accurately model flow through the microvasculature . Multiple studies have investigated the combined use of microfluidic techniques with RBC image analysis to assess cell deformability, but these systems focus on either single microchannels with low cell throughput or wide channels that measure bulk cell properties. Furthermore, these studies are limited due to the inability to accurately detect cell edges within microchannels that constrict individual cells.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics enables creating fluidic structures at the same scale as even the smallest blood vessels . Various microfluidic designs have been developed to interpret RBCs deformability . In some designs, transit of a single RBC through a channel slightly larger and wider than cell diameter is quantified, and deformability is inferred from the geometric shape of the transiting RBC .…”
mentioning
confidence: 99%